Effect of edible bird nest supplementation against busulfan-induced oligospermia in adult rats - Nurul Atiqah Azhar,; Khairul Osman,; Farah Hanan Fathihah Jaffar,; Chua, Kien Hui; Mohd Farisyam Mat Ros,; Aini Farzana Zulkefli,; Siti Fatimah Ibrahim, (Penerbit Universiti Kebangsaan Malaysia, 2024)
WHO estimates that between 48 million couples and 186 million individuals are facing infertility globally. Male infertility contributes to one-third of the problem with oligospermia as a primary underlying cause. Edible bird nest (EBN), a nutritional natural product, has the potential to improve male fertility status. However, the scientific evidence on oligospermia is sparse. Therefore, this study aimed to evaluate the effectiveness of EBN supplementation in busulfan-induced oligospermia of adult rats. Thirty-six eight-week-old Sprague Dawley male rats (N=36) were randomly and equally divided into six groups (n=6): Control, Sham, Busulfan, EBN 250, 500, and 1000 mg/ kg/daily. A single dose of 10 mg/kg busulfan was injected intraperitoneally to induce oligospermia. Daily EBN supplementation was administered for 28 consecutive days, started one day following the busulfan injection. Findings showed that sperm concentration, spermatogenesis index scoring, seminiferous tubule diameter, and germ cell height were reduced in busulfan-induced oligospermia. Meanwhile, the apoptosis status was significantly increased. EBN supplementation had significantly increased sperm concentration, spermatogenesis index scoring, germ cell height, and gene expression of p38 and MAPK14. EBN supplementation also reduced apoptosis in the oligospermia group in a dose-dependent manner. In conclusion, daily EBN supplementation has a protective effect in busulfan-induced oligospermia by increasing sperm production, preserving histological features of the testes, reducing apoptosis, and improving gene expression of p38 and MAPK14.